Body Composition and Physical Capacity in Patients with Covid-19 Hospitalized in a Intensive Care Unit; [Composición Corporal y Capacidad Física en Pacientes Con Covid-19 Hospitalizados en Una Unidad de Cuidados Intensivos] - Valenzuela-Vasquez, J; Del Valle-Valdes, M (Universidad de la Frontera, 2024)
The intensive care units (ICU) and acute care units have been the containers for the advance of the COVID-19 pandemic. However, prolonged stay in this unit can impact patients body composition (WC) and ability to exercise. This research aimed to determine if there is a relationship between body composition (BC) and the 6-minute walk test (6mWT). 17 people were recruited (8 women and 9 men). The following measurements were taken: 6mWT, its distance traveled (6mWTDT) and its speed (6mWTS) were considered. The WC variables measured were body mass index (BMI), fat mass (FM), fat-free mass (FFM), and lean mass (LM). 6mWTDT only showed a significant relationship with body LM (BLM). On the other hand, 6mWTS had a significant relationship with BLM. In addition to this, the FFM of the right lower limb and the FFM of the left lower limb showed a relationship with 6mWTS (r=0.422; p=0.041 and r=0.417; p=0.025, respectively). Also, the LM of the right lower limb and the LM of the left lower limb were significantly related to the 6mWTS (r=0.422; p=0.030 and r=0.420; p=0.042). In conclusion, there is a relationship between body composition and 6mWTS. This would allow us to quickly approach the level of functionality with which a patient enters a rehabilitation program. © 2024, Universidad de la Frontera. All rights reserved.